Pengembangan UMKM Rowosari melalui Pengelolaan Sumber Daya Alam dan Peningkatan Pemasaran Secara Online - Widowati Widowati; Satriyo Adhy; Titik Ekowati; Eka Triyana (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Rowosari Village is one of the villages located in the Tembalang District of Semarang, which has abundant and diverse Natural Resources (SDA) from various sectors. Through Micro, Small, and Medium Enterprises (MSMEs), the processing of natural resources contributes to economic growth and job creation. In addition, MSMEs also play an important role in driving economic activity through digital transformation. The purpose of this community service activity is to provide skills and additional knowledge needed by MSME actors. The methods used include mentoring and training in natural resource management, utilizing existing natural resource potential such as eggshells and onion skins. Furthermore, training in improving online product marketing was conducted. The result of this service activity is the enhancement of community capabilities by utilizing natural resources to boost MSME economies through digital transformation to expand market areas via online media.